TEACHING SPECIFIC TERMS IN ENGLISH CLASSES FOR ECONOMISTS - Aziza Togaeva (Galaxy International Interdisciplinary Research Journal, 2024)
This article discusses teaching English for specific purposes (ESP) in higher education institutions. Moreover, it focuses on the English classes for economic students based on specific terminology. Suggestions will be given for organizing practical lessons using pedagogical technologies for future economists.